Madeleine Parent: Activist - Lévesque, Andrée (Sumach Press, 2005)
"[B]rings together some of the papers presented at the conference, "Madeleine Parent, ses lutes et ses engagements /Madeleine Parent and her struggles," held in March 2001 at McGill University under the auspices of the Quebec Studies Programme and the McGill Centre for Research and Teaching on Women." – Editor. Translation of: Madeleine Parent, militante (2003). Contents: Portfolio of photographs – Introduction: setting the stage; Student life at McGill, 1936-1940 / Andrée Lévesque – Textile strikes in Quebec: 1946, 1947, 1952 / Denyse Baillargeon – Carrying on the struggle in Ontario, 1952-1973 / John Lang – The Atlantic connection / John St-Amand – The women's movement in Canada: setting the agenda / Lynn Kaye & Lynn Mcdonald – The importance of being Madeline: how an inactivist won the heart of Quebec's immigrant and minority women – A tribute to a valiant lady / Françoise David – Madeleine Parent: an unfailing ally of native women / Michèle Rouleau – An iron will and a string of pearls / Rick Salutin – A friend, a role model / Monique Simard.
Keywords: Feminism; History; Parent; Madeleine; 1918-2012; Social conditions; Syndicalism; Women political activists